A Novel Restorative Pulmonary Valve Conduit: Early Outcomes of Two Clinical Trials - Morales, David L.; Herrington, Cynthia; Bacha, Emile A.; Morell, Victor O.; Prodán, Zsolt; Mroczek, Tomasz; Sivalingam, Sivakumar; Cox, Martijn; Bennink, Gerardus; Asch, Federico M. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: We report the first use of a biorestorative valved conduit (Xeltis pulmonary valve - XPV) in children. Based on early follow-up data the valve design was modified; we report on the comparative performance of the two designs at 12 months post-implantation. Methods: Twelve children (six male) median age 5 (2 to 12) years and weight 17 (10 to 43) kg, had implantation of the first XPV valve design (XPV-1, group 1; 16 mm (n=5, and 18 mm (n=7). All had had previous surgery. Based on XPV performance at 12 months, the leaflet design was modified and an additional 6 children (5 male) with complex malformations, median age 5 (3 to 9) years, and weight 21 (14 to 29) kg underwent implantation of the new XPV (XPV-2, group 2; 18mm in all). For both subgroups, the 12 month clinical and echocardiographic outcomes were compared. Results: All patients in both groups have completed 12 months of follow-up. All are in NYHA functional class I. Seventeen of the 18 conduits have shown no evidence of progressive stenosis, dilation or aneurysm formation. Residual gradients of >40 mm Hg were observed in three patients in group 1 due to kinking of the conduit (n=1), and peripheral stenosis of the branch pulmonary arteries (n=2). In group 2, one patient developed rapidly progressive stenosis of the proximal conduit anastomosis, requiring conduit replacement. Five patients in group 1 developed severe pulmonary valve regurgitation (PI) due to prolapse of valve leaflet. In contrast, only one patient in group 2 developed more than mild PI at 12 months, which was not related to leaflet prolapse. Conclusions: The XPV, a biorestorative valved conduit, demonstrated promising early clinical outcomes in humans with 17 of 18 patients being free of reintervention at one year. Early onset PI seen in the XPV-1 version seems to have been corrected in the XPV-2, which has led to the approval of an FDA clinical trial.